When they see us: a critical analysis of racialized experiences within multiple contexts while residing within the United States - Clark, Kennedy (Kansas State University, 2022)
The following three studies examine racialized and cultural experiences in various contexts in the United States. These studies utilized quantitative analyses to explore the concept of counter-storytelling and its importance in research. These studies sought to examine differences between cultural groups when responding to the same question. The first study explored the internalization of racialized experiences identified among Black and white populations; the results demonstrated that racialized experiences have effects on the two communities of interest. The second study sought to explore experiences related explicitly to the cultural affiliation of Black mothers and empathy outcomes for their adolescents; the findings demonstrated that adolescents who have mothers with higher levels of engagement and neighborhood involvement rate higher on the empathy measure used within the study. The final study is a comparative analysis that demonstrates the importance of research analyzing data and allowing space for the various findings among racial and cultural groups; the most important finding is that no two groups shared identical findings.
Keywords: Race